GENDER FLUIDITY OF DSD CHARACTERS IN MIZUSHIRO SETONA'S HOUKAGO HOKENSHITSU MANGA - Rahman, Aulia; Rachmidian, Rahayu (Hikari: Jurnal Bahasa dan Kebudayaan, 2025)
This research is entitled "Gender Fluidity of DSD Characters in Mizushiro Setona's Houkago Hokenshitsu Manga". The main focus of this study is on the concept of gender identity fluidity displayed by DSD (Disorder of Sexual Development) characters and their relationship to the issue of freedom. This study was conducted by utilizing references to Gender Fluidity proposed by Erin Calhoun Davis. In general, gender fluidity is understood as the uncertainty of gender identity that arises as a result of the destabilization of the binary gender system. Mizushiro Setona uses literary works as a tool to convey messages that contain social criticism of the injustices experienced by minority groups. The transgender character is used as the main character who seeks to break free from the shackles of social norms. The concept of gender fluidity from Erin Calhoun Davis shows that there is a possibility for gender diversity for individuals because identity formation is a process that never stops and always continues. This concept of gender fluidity is used as a reference in research on DSD individuals. The findings of this study show that DSD individuals face pressure due to external pressures. The pressure comes from gender boundaries that are debated in society. Gender attributes are used by trans individuals to free the body and soul from the shackles of gender norms. Although DSD individuals can achieve freedom through appearance and gender attributes, it is limited to internal aspects. Keywords: Gender Fluidity, DSD, Manga